Exploring Hans Küng’s Paradigm Theory for Understanding Religion: An Islamic Perspective - Che Nordin, Mohd Khairul Naim (Jurnal Usuluddin, 2023)
This article discusses the paradigm theory and its application to understanding religion, with a focus on the perspective of Islam. Hans Küng’s paradigm theory is examined, which involves analyzing religious paradigms and their changes to understand religion comprehensively. The article explains that Küng’s approach involves examining several aspects of religion, such as its history, development, current situation, and predictions or assumptions about its future based on its history and current situation. However, the article also highlights some questions regarding the methodology used by Küng to identify the stages of the paradigm and the shifts that occur. Additionally, the article notes that understanding religion based on paradigm theory is not sufficient to adequately describe the identity of a religion. Overall, this article sheds light on the strengths and limitations of using paradigm theory to understand religion, particularly from an Islamic perspective. Therefore, a nuanced understanding of Islam requires sensitivity to its unique theological and textual contexts.